The Ecuadorian Society Analyzed from the Cultural Dimensions - Aguilar-Rodríguez, Iliana (2018)
The cultural dimensions of the Ecuadorian society were oriented according to the Hofstede model, which are evaluated on a scale from 1 to 100, which implies measuring the variability between them: Equality versus inequality of economic and social power; individualism compared to collectivism; masculinity and femininity; avoid uncertainty as opposed to tolerance; indulgence against restriction and short-term orientation compared to the long term. An exploratory study was applied by secondary sources, which determined that Ecuador is located as a collectivist society that considers that it belongs to a very important group. Likewise, religion and superstition have great prominence, being the tradition respected by its members. Consider that society is always different when a power authority leads to a change that groups its followers. In this society people seek status and rewards linked to performance, but often sacrifices leisure in relation to work.